Optical stochastic cooling for RHIC using optical parametric amplification - M. Babzien; I. Ben-Zvi; I. Pavlishin; I. V. Pogorelsky; V. E. Yakimenko; A. A. Zholents; M. S. Zolotorev (Physical Review Special Topics. Accelerators and Beams, 2004)
We propose using an optical parametric amplifier, with a ∼12   μm wavelength, for optical-stochastic cooling of ^{79}Au ions in the Relativistic Heavy Ion Collider. While the bandwidth of this amplifier is comparable to that of a Ti:sapphire laser, it has a higher average output power. Its wavelength is longer than that of the laser amplifiers previously considered for such an application. This longer wavelength permits a longer undulator period and higher magnetic field, thereby generating a larger signal from the pickup undulator and ensuring a more efficient interaction in the kicker undulator, both being essential elements in cooling moderately relativistic ions. The transition to a longer wavelength also relaxes the requirements for stability of the path length during ion-beam transport between pickup and kicker undulators.